4-Methoxy-2,2′-bipyrrole-5-carbaldehyde, a biosynthetic intermediate of bipyrrole-containing natural products from the Streptomyces culture, arrests the strobilation of moon jellyfish Aurelia coerulea - Misaki, Yuya; Hirashima, Tomomi; Fujii, Karin; Hirata, Asahi; Hoshino, Yutaro; Sumiyoshi, Miho; Masaki, Sachiko; Suzuki, Toshihiro; Inada, Kuninobu; Koyama, Hiroki; Kuniyoshi, Hisato; Arakawa, Kenji (Frontiers in Marine Science, 2023)
Streptomyces spp. are well-known producers of secondary metabolites with diverse biological activities. We screened the substances that regulate polyp-to-jellyfish transition, called strobilation, of the moon jellyfish (Aurelia coerulea) from the Streptomyces culture library. Among the culture extracts of the strains tested, Streptomyces albus HUT6047 inhibited the strobilation of A. coerulea. The active component in strain HUT6047 was purified. Based on structure elucidation, this component was identified as 4-methoxy-2,2′-bipyrrole-5-carbaldehyde (MBC), a possible common biosynthetic intermediate of pyrrole-containing natural products including prodigiosins and tambjamines. Synthetic MBC arrested strobilation without inducing cytotoxicity and generated abnormal tentacle-like structures in a dose-dependent manner. Synthetic MBC also exhibited a minimum activity of 6.3 µM. To our knowledge, this study provides the first example of a biological activity of MBC.